2017
DOI: 10.3390/s17040805
|View full text |Cite
|
Sign up to set email alerts
|

A High Spatial Resolution Depth Sensing Method Based on Binocular Structured Light

Abstract: Depth information has been used in many fields because of its low cost and easy availability, since the Microsoft Kinect was released. However, the Kinect and Kinect-like RGB-D sensors show limited performance in certain applications and place high demands on accuracy and robustness of depth information. In this paper, we propose a depth sensing system that contains a laser projector similar to that used in the Kinect, and two infrared cameras located on both sides of the laser projector, to obtain higher spat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The performed experiments yielded higher performance in Kinect v2 ToF sensor with less noisy and denser 3D information. Another comparison in [ 210 ] was performed based on two SL sensors (Kinect v1, Asus Xtion Pro), one ToF (Kinect v2), and one ASV sensor (Intel R200). The comparison yielded to the same results and conclusions as [ 209 ], and showed that the Kinect v2 ToF sensor surpasses the rest of the three devices and presents higher spatial resolution…”
Section: Resultsmentioning
confidence: 99%
“…The performed experiments yielded higher performance in Kinect v2 ToF sensor with less noisy and denser 3D information. Another comparison in [ 210 ] was performed based on two SL sensors (Kinect v1, Asus Xtion Pro), one ToF (Kinect v2), and one ASV sensor (Intel R200). The comparison yielded to the same results and conclusions as [ 209 ], and showed that the Kinect v2 ToF sensor surpasses the rest of the three devices and presents higher spatial resolution…”
Section: Resultsmentioning
confidence: 99%
“…In another study by Ross et al [ 45 ], the mean discrepancy of scan data obtained using smartphones ranged from 0.9 mm to 1.0 mm, depending on the number of photographs taken during scanning. In recent years, infrared structured-light depth-sensing cameras have been incorporated in mobile devices to facilitate 3D optical scans [ 51 ]. 3D depth-sensing cameras work by the time-of-flight principle, measuring the time taken for light emitted by an illumination unit to travel to an object and back to the sensor array [ 52 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…These technologies use an artificial source of light such as laser or LED source of different wavelengths notably infrared or near infrared, to illuminate the scene and analyze the reflected light. Numerous studies have compared these two imaging technologies, 59,60 demonstrating that SL‐based systems have lower resolution and accuracy, and their performance is inferior when dealing with moving objects or dynamic scenes 61,62 . In Ref.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have compared these two imaging technologies, 59,60 demonstrating that SL-based systems have lower resolution and accuracy, and their performance is inferior when dealing with moving objects or dynamic scenes. 61,62 In Ref. [63], the author reported that ToF cameras do not suffer as much from occlusion in contrast to SL cameras.…”
Section: A Range Imaging Sensorsmentioning
confidence: 99%